THE APPLICATION OF APPLIED BEHAVIOR ANALYSIS (ABA) IN THE DEVELOPMENT OF INCLUSIVE PRODUCTS FOR CHILDREN WITH AUTISM - Silva, Jammylly Fonseca (Revista Sistemática, 2023)
Applied Behavior Analysis (ABA) has long been recognized as an effective therapeutic approach for individuals with Autism Spectrum Disorder (ASD), primarily within clinical and educational settings. However, the potential of ABA principles extends beyond these traditional environments, offering valuable insights into the design of inclusive products tailored to the unique needs of autistic children. This paper explores the interdisciplinary application of ABA in the development of products such as adaptive toys, clothing, and footwear, aiming to enhance the daily experiences and developmental outcomes of children with ASD. The integration of ABA strategies into product design involves a meticulous understanding of behavioral patterns, sensory preferences, and reinforcement mechanisms. By aligning product features with these behavioral insights, designers can create items that not only accommodate sensory sensitivities but also promote engagement, learning, and independence. For instance, toys designed with ABA principles can reinforce positive behaviors and facilitate social interactions, while adaptive clothing can address sensory discomforts and support self-dressing skills. This paper conducts a comprehensive literature review of recent studies that exemplify the successful incorporation of ABA into product design for autistic children. The findings underscore the significance of a collaborative approach, bringing together behavior analysts, designers, and stakeholders to create products that are both functional and empathetic. By embracing the principles of ABA in product development, we can move towards a more inclusive society that recognizes and supports the diverse needs of children with autism.